Effect of different anesthetic mixtures—ketamine‐xylazine, ketamine‐acepromazine and tiletamine‐zolazepam—on the physiological and blood biochemistry parameters of male rhesus monkeys (Macaca mulatta) at different ages. Issue 2 (27th March 2019) - Hernández‐Godínez, Braulio; Bonilla Jaime, Herlinda; Poblano, Adrián; Arteaga‐Silva, Marcela; Medina Hernández, Ameyalli; Contreras‐Uribe, Armando; Ibáñez‐Contreras, Alejandra
Abstract: Background: Anesthetic agents are commonly utilized in the handling of non‐human primates for prevent the stress caused in physical exploration or physical restrain. For this reason, the objective of this work was to describe the effect of age and dissociative anesthetics (ketamine and tiletamine), and their combinations with acepromazine, xylazine and zolazepam, on the physiological and blood biochemical parameters in Macaca mulatta . Methods: Eighty male Macaca mulatta were divided into four experimental groups depending on the anesthetic mixture applied. Each group of 20 males was divided into five sub‐groups according to age. Physiological parameters were recorded every 5 minutes during a 30‐minute period. A blood sample was drawn to analyze blood biochemistry. Results: Statistical analyses revealed significant differences in the physiological parameters between the ketamine‐acepromazine and ketamine‐xylazine groups compared to the control group. The analysis of blood biochemistry found significant differences by age and by anesthetic mixture among all groups. Conclusion: These findings contribute to standardizing this animal model in biological research.